How to Join the European Union? : Text is published in periodical "Survey" 3-4, 2005 - Ćećez, Momir (Pregled: časopis za društvena pitanja / Periodical for social issues, 2008)
There is a clear determination of all political, state and other structures in Bosnia and Herzegovina for accession to the European Union. All activities of the state and social institutions are directed towards that goal.